2017
DOI: 10.5625/lar.2017.33.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic effect of novel extracts from mulberry (Morus alba) leaves fermented withCordyceps militarisin the primary adipocytes derived from SD rats

Abstract: Mulberry (Morus alba) leaves are known to have therapeutic effects on lipid metabolism including lipogenesis, lipolysis and hyperlipidemia. However, novel compounds with strong lipolytic ability among 27 extracts of the mulberry leaves fermented with Cordyceps militaris (EMfCs) have not yet been identified. Therefore, the cAMP concentration and cell viability were measured in the primary adipocytes of SD (Sprague Dawley) rats and 3T3-L1 cells after treatment of 27 EMfCs. Briefly, mulberry leaves powders amende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…SVF was isolated from inguinal white adipose tissue (iWAT) of 6-week-old male Wild-type or Ahnak Knock-out mice 35 . Briefly, the adipose tissue was digested with 0.075% collagenase type II (Worthington Biochemical Corporation, Lakewood, NJ, USA) containing 1% bovine serum albumin (BSA) for 2 h at 37 °C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…SVF was isolated from inguinal white adipose tissue (iWAT) of 6-week-old male Wild-type or Ahnak Knock-out mice 35 . Briefly, the adipose tissue was digested with 0.075% collagenase type II (Worthington Biochemical Corporation, Lakewood, NJ, USA) containing 1% bovine serum albumin (BSA) for 2 h at 37 °C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…EMfCs used in this study were prepared in accordance with the previous papers [14]. Briefly, the samples of mulberry dry leaves were collected from plantations in the Sangju district of Korea in October 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports indicate that C. militaris -fermented products are beneficial in attenuating liver fibrosis (24,25); similar effects were observed with a mixture of C. militaris and a secondary metabolite secreted from mushroom (26). In our previous study, we reported that the extract of Morus alba leaves fermented with C. militaris (EMfC) has a lipolytic effect on adipocytes isolated from SD rats (27). However, no detailed study was performed to evaluate the inhibitory effect of EMfC on obesity.…”
Section: Introductionmentioning
confidence: 99%